Evaluation of Patterns of Beta Thalassaemia in Children with Microcytic Hypochromic Anemia (Medical Forum Monthly, 2024)
Objective: The aim of this study was to evaluate the patterns of Beta Thalassaemia in children suffered with microcytic hypochromic anemia in the different hospitals of Hyderabad region. Study Design: Cross sectional study.Place and Duration of Study: This is an experimental based research study that was conducted at Isra University Hospital, Hyderabad and Liaquat University of Medical and Health Sciences Hospital Jamshoro Hyderabad from June 2011 to February 2012.Materials and Methods: Hundred (100) children from either gender attending outpatient department of Isra University Hospital and Liaquat University Hospital Hyderabad were selected for this study. Whole blood sample (10ml) was collected from each children. Peripheral smears were made and found that all children have suffered with findings of microcytic hypochromic anemia. Children with other than microcytic hypochromic anemia were excluded from this study. All parents of children were interviewed regarding family history and marriages with cousin and other findings or histories were also recorded on a well designed performa.Results: Whole blood samples were analyzed for the evaluation of the patterns of Beta Thalassaemia in 100 children who were affected with microcytic hypochromic anemia. Out of 100 children, 08 of them were diagnosed as having beta thalassaemia minor, one as Beta Thalassaemia major and the remaining 91 were non thalassaemics. Among 08 Beta Thalassaemic minor children, 05 were females and 03 were males and only one male child was suffered with beta thalassaemia major.Conclusion: It is concluded that the prevalence level of beta thalassaemia is higher in Hyderabad, which is an alarming. Many factors such as poor facilities for diagnosis, lack of awareness among clinicians, consultants and pathologists and high cost of molecular diagnosis play a contributory role in the propagation of the beta thalassaemia in the Pakistani population. These factors become a serious hindrance for the prevention of thalassaemic program in Pakistan